Methimazole-Induced ANCA Vasculitis: A Case Report - Precil Diego Miranda de Menezes Neves (Diagnostics, 2021)
Rapidly progressive glomerulonephritis (RPGN) is a syndrome which presents rapid loss of renal function. Vasculitis represents one of the major causes, often related to anti-neutrophil cytoplasmic antibodies (ANCA). Herein, we report a case of methimazole-induced ANCA-associated vasculitis. A 35-year-old woman complained of weight loss and fatigue for 2 weeks and attended the emergency room with alveolar hemorrhage. She had been diagnosed with Graves’ disease and had been taking methimazole in the past 6 months. Her physical examination showed pulmonary wheezing, hypertension and signs of respiratory failure. Laboratory tests revealed urea 72 mg/dL, creatinine 2.65 mg/dL (eGFR CKD-EPI: 20 mL/min/1.73 m2), urine analysis with >100 red blood cells per high-power field, 24 h-proteinuria: 1.3 g, hemoglobin 6.6 g/dL, white-cell count 7700/mm3, platelets 238,000/mm3, complement within the normal range, negative viral serological tests and ANCA positive 1:80 myeloperoxidase pattern. Chest tomography showed bilateral and diffuse ground-glass opacities, and bronchial washing confirming alveolar hemorrhage. A renal biopsy using light microscopy identified 27 glomeruli (11 with cellular crescentic lesions), focal disruption in glomerular basement membrane and fibrinoid necrosis areas, tubulitis and mild interstitial fibrosis. Immunofluorescence microscopy showed IgG +2/+3, C3 +3/+3 and Fibrinogen +3/+3 in fibrinoid necrosis sites. She was subsequently diagnosed with crescentic pauci-immune glomerulonephritis, mixed class, in the setting of a methimazole-induced ANCA vasculitis. The patient was treated with methimazole withdrawal and immunosuppressed with steroids and cyclophosphamide. Four years after the initial diagnosis, she is currently being treated with azathioprine, and her exams show creatinine 1.30 mg/dL (eGFR CKD-EPI: 52 mL/min/1.73 m2) and negative p-ANCA.